Wrapping Papers from Enterolobium timbouva - Dhawan, Rita; Karira, B. G. (Indian Forester, 1984)
Laboratory scale experiments on the production of sulphate pulps for wrapping paper from Enterolobium timbouva were carried out. Proximate chemical analysis and fibre dimensions were also determined. The results indicate that Enterolobium timbouva is a suitable raw material for the production of wrapping paper.